ADABIYOTDA BADIIY MAHORAT HAQIDA (T.Qayipbergenovning «Uyqısız túnler» povesti asosida) - Sarsenbaev, Q.J. (SCIENCE and SOCIETY, 2022)
The article touches upon the problem of mastering the theory of literature. He also touched upon the level of study of artistic mastery in the great similar works of world literature and Karakalpak literature. Examples of the article are taken from the story " Uyqısız túnler" by the People's Writer of Uzbekistan and Karakalpakstan, Hero of Uzbekistan T. Kaiypbetrgenov.
Keywords: literature; skill; writer; story; image; literary critic